Sustainable Extraction of Cinnamon Phenolics through Synergy of Green Solvents and Microwave-Assisted Technology - Nanin Agustin; Devi Yuni Susanti; Muhammad Prasetya Kurniawan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Increasing global awareness of environmental issues has encouraged the development of sustainable and eco-friendly methods for extracting phenolic compounds from Cinnamomum burmannii. This study integrates Microwave-Assisted Extraction (MAE) with Natural Deep Eutectic Solvents (NaDES) as a green extraction approach. The objectives were to evaluate thermal efficiency, energy consumption, carbon emissions, and extraction kinetics at microwave powers of 640, 720, and 800 W using citric acid–sucrose as the solvent. The highest thermal efficiency (69.82%) was achieved at 640 W, with an energy consumption of 540.86 kJ and carbon emissions of 0.131 kg CO₂e. Extraction kinetics were described using the Peleg model, which accurately represented changes in phenolic concentration during extraction. The highest extraction rate constant (B₀ = 0.2117 mg/mL·min) was obtained at 640 W, while the highest equilibrium capacity constant (Ce = 0.6982 mg/mL) and total phenolic content (6.42 ± 0.046 mg GAE/mL) were achieved at 800 W. These findings indicate that increasing microwave power enhances both extraction rate and phenolic yield. Compared with conventional methods, MAE combined with NaDES demonstrated lower energy consumption and reduced carbon emissions, highlighting its potential as a sustainable extraction technology.